(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
It is shown that the financial stability of economic entities increases the role of rational use of financial resources of enterprises, it is possible to ensure its constant financial balance during the development of the enterprise, to ensure sufficient financial control of the enterprise by the founders of the enterprise, to ensure sufficient financial flexibility of the enterprise, to ensure timely reinvestment of capital.